The role of screening and surveillance in the detection of childhood vision impairment and blindness in the UK. Issue 9 (5th May 2022) - Solebo, Ameenat Lola; Teoh, Lucinda; Rahi, Jugnoo Sangeeta
Abstract : Objective: Understanding pathways to detection for childhood visual impairment (VI) is critical for planning services. We aimed to describe patterns of detection for childhood VI. Design and setting: Cross-sectional study using data from British Childhood Visual Impairment and Blindness Study 2. Patients: Children newly diagnosed with VI, severe vision impairment or blindness (SVI/BL)—that is, visual acuity worse than logMAR 0.5 in both eyes—were identified through active surveillance, with data collection at diagnosis and 1 year later. Outcome measure: Method of detection of vision/eyes problem. Results: 784 children (45%, 356 girls) were identified, of whom 313 (40%) had VI, 471 (60%) had SVI/BL. Additional non-ophthalmic disorders or impairments (VI/SVI/BL 'plus'), were diagnosed in 72% (559/784). Of the 784, 173 children were detected through routine screening (22%), 248 through targeted examinations (32%) and 280 through family self-referral (36%). Parents and carers had only reported symptoms in 55% of children who manifested them, with evidence that families living in socioeconomically deprived areas were less likely to report concerns. Paediatricians were the professionals most likely to raise initial suspicion of visual disability. Conclusions: Our findings show that targeted screening and surveillance is important for the detection of full spectrum childhood visual impairment (VI/SVI/BL), as a significant proportion of children will not have symptoms, or their parents or carers will not report symptoms. As paediatricians were the professionals most commonly involved in detection, it would be helpful if their core competencies included the skills needed to undertake simple assessments of vision. Abstract : Data from the British Childhood Visual Impairment and Blindness Study 2 is examined in this study, focusing on the patterns of detection for childhood visual impairment. A significant percentage of children with visual impairment were found to have had no reported visual symptoms at the time of diagnosis, highlighting the need for vigilance for these problems in at risk children.